Progresses and challenges of engineering thermophilic acetogenic cell factories - Bourgade, Barbara; Islam, M. Ahsanul (Frontiers in Microbiology, 2024)
Thermophilic acetogens are gaining recognition as potent microbial cell factories, leveraging their unique metabolic capabilities to drive the development of sustainable biotechnological processes. These microorganisms, thriving at elevated temperatures, exhibit robust carbon fixation abilities via the linear Wood-Ljungdahl pathway to efficiently convert C1 substrates, including syngas (CO, CO2 and H2) from industrial waste gases, into acetate and biomass via the central metabolite acetyl-CoA. This review summarises recent advancements in metabolic engineering and synthetic biology efforts that have expanded the range of products derived from thermophilic acetogens after briefly discussing their autotrophic metabolic diversity. These discussions highlight their potential in the sustainable bioproduction of industrially relevant compounds. We further review the remaining challenges for implementing efficient and complex strain engineering strategies in thermophilic acetogens, significantly limiting their use in an industrial context.